Exploring the interaction between internal communication and organizational behavior in enhancing job satisfaction - Han Juan; Chiew Tung Moi (Journal Of Electrical Systems, 2024)
This research investigates the intricate relationships between Internal Communication, Organizational Behavior, Employee Motivation, and Job Satisfaction within organizational settings. The main objective is to understand how these factors interact to influence job satisfaction and to inform policy development aimed at enhancing workplace environments. Utilizing a quantitative approach, data were collected through a questionnaire from 378 respondents and analyzed using Structural Equation Modeling (SEM) via SmartPLS and descriptive statistics using SPSS. The results reveal that Employee Motivation significantly and positively affects Job Satisfaction (coefficient = 0.578, p < 0.001), while Organizational Behavior has a substantial impact on both Employee Motivation (coefficient = 0.722, p < 0.001) and Job Satisfaction (coefficient = 0.176, p = 0.003). Internal Communication, however, shows a significant but modest positive effect on Job Satisfaction (coefficient = 0.079, p = 0.043) and no significant impact on Employee Motivation. These findings suggest that while effective communication is essential, it needs to be complemented by strong organizational practices to enhance motivation and satisfaction. The policy implications underscore the importance of fostering motivational strategies and supportive organizational cultures to improve job satisfaction. This research contributes to the understanding of organizational dynamics and provides actionable insights for improving employee well-being and performance.